Digital Marketing Adoption Between Rice Farmer and Farm Trader - Makbul, Yogi; Rochana, Siti Herni; Nugraha, Deni; Ratnaningtyas, Sudrajati (Archives of Business Research, 2022)
Rice marketing, largely, is still traditional, wherein farmers sell their products to traders, who then sell them to consumers. On the other hand, the use of digital media is fast developing in society currently. It is also growing in rice marketing. Digital media can be utilized by farmers to shift from traditional marketing channels to direct online marketing to consumers. The question is which category, i.e., farmers, or traders, can better adopt digital marketing. The purpose of this study is to compare the adoption rate of digital marketing between farmers and traders. If this adoption is higher, then there is a possibility of direct online marketing replacing the traditional ways of rice marketing. The research was conducted by surveying farmers and traders in certain rice production centers in Indonesia. The location of the research was Gantar District in Indramayu Regency, West Java province. The location was chosen because Gantar District is the highest rice producer in Indramayu Regency; furthermore, this Regency is the largest rice producer in West Java. The province of West Java is the ultimate rice producer in Indonesia. The results show that the digital media adoption of traders is higher than that of farmers. So, the possibility of a shift to online marketing from farmers to consumers is low possibility.